The German coal debate on Twitter: Reactions to a corporate policy process. (October 2022) - Müller-Hansen, Finn; Lee, Yuan Ting; Callaghan, Max; Jankin, Slava; Minx, Jan C.
Abstract: Phasing out coal is a prerequisite to achieving the Paris climate mitigation targets. In 2018, the German government established a multi-stakeholder commission with the mandate to negotiate a plan for the national coal phase-out, fueling a continued public debate over the future of coal. This study analyzes the German coal debate on Twitter before, during, and after the session of the so-called Coal Commission, over a period of three years. In particular, we investigate whether and how the work of the commission translated into shared perceptions and sentiments in the public debate on Twitter. We find that the sentiment of the German coal debate on Twitter becomes increasingly negative over time. In addition, the sentiment becomes more polarized over time due to an increase in the use of more negative and positive language. The analysis of retweet networks shows no increase in interactions between communities over time. These findings suggest that the Coal Commission did not further consensus in the coal debate on Twitter. While the debate on social media only represents a section of the national debate, it provides insights for policy-makers to evaluate the interaction of multi-stakeholder commissions and public debates. Highlights: We analyze the debate about the coal phase out in Germany on Twitter (2017–2020). We find that public attention, negative sentiment and polarization increased. In 2019, the Coal Commission agreed on a plan to manage the coal phase out. This compromise did not translate to more consensus in the public debate on Twitter.